A Study of the Significance of Mini Cement Plants in Building A Self-Reliant Economy - Rashmi Sharma,; Dr. Surajit Kr. Bhagowati,; Dr. Surajit Kr. Bhagowati, (International Journal of Engineering and Management Research, 2023)
Nowadays, usage of cement is recognized as the most influential yardstick of urbanization vis-à-vis development of the economy. With the increasing demand for this wonder material, the mini cement plants are emerging as the counterpart of large plants in making the material available in the remotest of locality. In this process, they are remarkably fostering self-reliance while giving due consideration to environmental protection too. In this paper, attempts have been made to highlight the significance of mini cement plants in encouraging local entrepreneurship along with shaping a concrete economy for the region. The study will also try to analyze the performance, problems, and prospects of the mini cement plants along with the extent to which various factors influence their existence in the region of study.